PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA GAMBAR TIGA DIMENSI TERHADAP KREATIVITAS MENGGAMBAR SISWA MATERI SBDP - Gusti Ulfa Sari; Noviati; Rury Rizhardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the implementation of the Project Based Learning model assisted by three-dimensional image media on students’ drawing creativity in SBDP subject at SD Negeri 38 Palembang. This study used a quasi- experimental quantitative method with a Nonequivalent Control Group Pretest-Posttest Design. The sample consisted of an experimental class and a control class. Data collection techniques were conducted through observation and assessment of students’ drawing creativity. Data analysis was carried out using normality test, homogeneity test, and hypothesis testing (independent sample t-test) with the assistance of SPSS application. The results showed that the average score of students’ drawing creativity in the experimental class was 13.35 with a standard deviation of 2.262, while the control class obtained an average score of 11.25 with a standard deviation of 2.436. The hypothesis test result showed a significance value (Sig. 2-tailed) of 0.008 ≤ 0.05, therefore H0 was rejected and H1 was accepted. This indicates that the implementation of the Project Based Learning model assisted by three-dimensional image media had a significant effect on students’ drawing creativity in SBDP subject at SD Negeri 38 Palembang.